The Peaceful Valley crime wave - Pronzini, Bill (Forge, 2019)
In the quiet town of Peaceful Valley, Montana, Sheriff Lucas Monk must deal with an unexpected crime wave, which is ignited by the theft of a wooden cigar store Indian.